Delivery of all trans-retinoic acid (RA) to hepatocyte cell line from RA/galactosyl alpha-cyclodextrin inclusion complex - Seo, SJ; Kim, SH; Sasagawa, T; Choi, YJ; Akaike, T; Cho, CS (ELSEVIER SCIENCE BV, 2004)
All trans-retinoic acid (RA) plays a role in regulation of P450RAI gene expression. In this study, hepatocyle cell line (HepG2) was used to study an effect of RA released from RA/galactosyl alpha-cyclodextrin (GCD) inclusion complex on regulation of P450RAI gene expression. A delivery system composed of RA/GCD inclusion complex was applied because RA is poorly water soluble, and organic solvents used to dissolve it often interfere with cytotoxicity. Solubility of RA in water was increased by forming complex with GCD. Inclusion complex between GCD and RA was checked by H-1-nuclear magnetic resonance, Fourier transformation infrared (FT-IR) spectroscopy and X-ray diffraction (XRD). The chemical shifts of the interior and exterior GCD protons in the presence of RA indicated that the RA was included within the GCD macrocycle cavity. The carbonyl band of RA and crystalline peak of RA in RA/GCD inclusion complex disappeared from FT-IR and XRD measurements, respectively, indication of inclusion complex between RA and GCD. From the observation of fluorescence micrograph of hepatocytes and flow cytometry measurement of HepG2, the internalization of fluorescein isothiocyanate-GCD by the hepatocyte occurred. Gene expression of P450RAI in HepG2 by delivery of RA from RA/GCD complex was observed. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: DRUG-DELIVERY; X-RAY; LIVER; NANOPARTICLES; 4-HYDROXYLASE; RECEPTORS; CYP26; RECOGNITION; EXPRESSION; CARRIERS